2018
DOI: 10.1007/s10815-018-1140-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of inhibitor proteins that control primordial follicle reserve decreases in cryopreserved ovaries after autotransplantation

Abstract: One of the causes of primordial follicle loss after transplantation of ovarian graft may be decreased expression of the inhibitory proteins that guard the ovarian reserve and transplantation itself seems to be the major cause for disruption of inhibitory molecular signaling. Our findings highlight important molecular aspects for future clinical applications for fertility preservation in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…SonerCelik et al [60] research team's findings regarding ovarian cryo-preservation and auto-transplantation demonstrate that expression of inhibitor proteins that control primordial follicle reserve decreases in cryopreserved ovaries after transplantation. The observation is consistent with the ovarian activity rush observed by others [61,62], and thus they debate the recommendation of follicular activation prior (in vitro activation IVA) to transplantation [58,63]. The longevity of the transplanted ovarian tissue varies widely and may depend on the age of the woman at cryo-preservation [64], some blaming the revascularization rate after transplantation as an important issue [65]; however, long functioning viability of more than ten years has been reported [66].…”
Section: New Techniques Of Fertility Preservationsupporting
confidence: 82%
“…SonerCelik et al [60] research team's findings regarding ovarian cryo-preservation and auto-transplantation demonstrate that expression of inhibitor proteins that control primordial follicle reserve decreases in cryopreserved ovaries after transplantation. The observation is consistent with the ovarian activity rush observed by others [61,62], and thus they debate the recommendation of follicular activation prior (in vitro activation IVA) to transplantation [58,63]. The longevity of the transplanted ovarian tissue varies widely and may depend on the age of the woman at cryo-preservation [64], some blaming the revascularization rate after transplantation as an important issue [65]; however, long functioning viability of more than ten years has been reported [66].…”
Section: New Techniques Of Fertility Preservationsupporting
confidence: 82%
“…A major obstacle of OTCTP is follicle loss due to, among other factors, accelerated recruitment of primordial follicles during the transplantation process [ 18 , 53 , 54 ]. Our first aim was to assess how cryopreservation itself impacts follicle activation.…”
Section: Discussionmentioning
confidence: 99%
“…Follicle activation after OTCTP is well documented in both preclinical and clinical studies [47][48][49][50][51][52]. The transplantation process itself is the major cause of accelerated recruitment of primordial follicles, and the PI3K/PTEN/ Akt and mTOR pathways are the main pathways involved in this phenomenon [18,53,54]. However, the contribution of the cryopreservation process to follicle activation is not yet well studied.…”
mentioning
confidence: 99%
“…Related to ischemia or not, the balance between activator and suppressor molecules in the ovary that normally keeps the dormant PFs from depletion is suggested to change instantly and a rapid burn-out leads to a significant follicle loss after OTC causing premature ovarian failure (POF) [13]. The authors recently showed that expression of inhibitor proteins, which control primordial follicle reserve, decreases in cryopreserved ovaries after autotransplantation [14]. Primordial follicles are aroused from a quiescence state by the interaction of various molecules to activate the PF growth, such as growth differentiation factor-9 (GDF-9), bone morphogenic protein-4/7/15 (BMP-4/7/15), Kit-ligand (KITL), leukemia inhibitory factor (LIF), and fibroblast growth factor (FGF-2), which are expressed in oocytes, granulosa cells, and stroma cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies on mice, it has been shown that rapamycin inhibits PF growth [21] and reverses the symptoms of ovarian hyperstimulation syndrome (OHSS) [22]. Based on the authors' recent findings about disrupted expression of inhibitor proteins after OTC and transplantation [14], the aim of this study was to investigate the effect of OTC on the expression of activator proteins that control follicle reserve and the protective potential of rapamycin treatment on PFs after vitrification/warming and re-transplantation in rats. As recent studies have demonstrated the importance of mTOR signaling pathway on PF survival and recruitment after various conditions [23], it was investigated whether PF burn-out after post-thaw and posttransplantation could be prevented by inhibiting the mTOR signaling pathway.…”
Section: Introductionmentioning
confidence: 99%